Coping with dysmenorrhea: a qualitative analysis of period pain management among students who menstruate - Fódhla Ní Chéileachair; Brian E. McGuire; Hannah Durand (BMC, 2022)
Abstract Background Dysmenorrhea, or period pain, affects up to 95% of menstruating individuals and is a common cause of educational absenteeism among students who menstruate worldwide. Evidence suggests that students may lack sufficient knowledge about their menstrual health, which may impede self-management. The aim of the current study was to explore pain management strategies used by students in Ireland with painful periods and to identify their unaddressed needs across physical, psychological, educational, and social domains. Methods This study used a qualitative, interpretive design and opportunity sampling approach to collect and interpret individual accounts of dysmenorrhea from third-level students in Ireland. Data from 21 students were collected using semi-structured online one-to-one interviews and analysed using reflexive thematic analysis. Results Analysis resulted in the construction of five themes: (1) Pain management is self-directed trial-and-error, (2) Home as safe haven, (3) Prioritising productivity over pain, (4) We're missing an option between 'normalise' and 'medicalise', and (5) Cycle of censorship and concealment. Overall, limited formal education on dysmenorrhea and prevailing negative attitudes towards menstruation create an unsupportive environment for students to learn adequate coping skills. Beyond education, menstrual stigma may also restrict the availability of clear management guidance in domestic and medical spheres. Experiences of dysmenorrhea were also influenced by the COVID-19 pandemic, where work-from-home measures were viewed favourably by individuals with dysmenorrhea. Conclusions This study indicates that students in Ireland are inadequately prepared to cope with dysmenorrhea. The current findings have substantial implications for evaluating and reforming current menstrual education standards, in addition to clarifying the negative effects of social stigma on menstrual health literacy.